2022
DOI: 10.1186/s12909-022-03571-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of introducing interprofessional education concepts on students of various healthcare disciplines: a pre-post study in the United Arab Emirates

Abstract: Background The value of interprofessional education (IPE) in nurturing healthcare professionals, and in shaping their professional identities, and their attitudes towards interdisciplinary teamwork and collaboration is established in the literature. IPE is an emerging concept in the Middle East and North Africa (MENA) region and is new to the United Arab Emirates (UAE). To date, the applicability and feasibility of IPE and of the corresponding collaborative practice in MENA countries remain lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…e special growth environment has cultivated the independent values of the "post-00s." According to social chemistry, people will produce certain values in the process of development to meet the social needs of the social environment [18], namely, self-awareness (define yourself according to the opinions and achievements in a field), reality (actively obtain resources to develop your field), adaptation (accept the differences between peers and yourself), adaptation (know who to show what image), equality (talk to anyone in the same way), care (care about your team) [19], and so om. e lifestyle of "post-00" groups living in various cultural exchanges is richer and more diverse, so it is reflected in the "post-00" ideology, that is, more diversified.…”
Section: Characteristics Of "mentioning
confidence: 99%
“…e special growth environment has cultivated the independent values of the "post-00s." According to social chemistry, people will produce certain values in the process of development to meet the social needs of the social environment [18], namely, self-awareness (define yourself according to the opinions and achievements in a field), reality (actively obtain resources to develop your field), adaptation (accept the differences between peers and yourself), adaptation (know who to show what image), equality (talk to anyone in the same way), care (care about your team) [19], and so om. e lifestyle of "post-00" groups living in various cultural exchanges is richer and more diverse, so it is reflected in the "post-00" ideology, that is, more diversified.…”
Section: Characteristics Of "mentioning
confidence: 99%
“…However, a recent study from UAE reported that students are willing for IPE and reported positive outcomes in terms of students' willingness to engage in inter-disciplinary learning and collaboration. 27 As reported in this research, students perceived team working skills to be vital for all healthcare students. These skills can be developed through IPE as reported by Shrader et al 46 wherein the authors found that community-based IPE could help health professional students develop their skills in collaborative practice.…”
Section: Discussionmentioning
confidence: 61%
“…However, a recent study from UAE reported that students are willing for IPE and reported positive outcomes in terms of students’ willingness to engage in inter-disciplinary learning and collaboration. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of literature has argued that IPE leads to improved patient outcomes and quality of care by team-working, shared decision-making, and increased patient satisfaction [3] [4]. Additionally, IPE is associated with increased job satisfaction among healthcare workers and improved e ciency and delivery of patient care.…”
Section: Introductionmentioning
confidence: 99%